Penggunaan E-Form untuk Meningkatkan Kepatuhan Wajib Pajak di SMAN 1 Binjai - Yunita Sari Rioni; Wan Fachruddin; Yurika Aulia (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Taxes function as a source of income for the state which is used to support development and finance various state needs. So far, taxpayer compliance has been the main focus of the Directorate General of Taxes. In an effort to increase the level of taxpayer compliance, the Directorate General of Taxes continues to innovate in providing services to taxpayers by developing an electronic system for the tax registration, payment and reporting process. Through this electronic system, the Directorate General of Taxes provides various conveniences, starting from the taxpayer registration process to tax reporting.